Gastric Outlet Obstruction – An Etiological Breakup - Arslan Shahzad ,Inayatullah Khan Adil, Mashood Ali, Muhammad Osama ,Mahrukh Laghari, Zain Sharif (Journal of Rawalpindi Medical College, 2017)
To evaluate the etiology of gastric outlet obstruction in Pakistani population. Methods: In this descriptive study patients with gastric outlet obstruction were included .All patients included in the study received intravenous fluids and electrolytes to correct dehydration and electrolyte imbalance. Nasogastric suction with gastric lavage was done. Diagnosis was established by UGI endoscopy and biopsy and was supported by CT scan and barium studies where required. Results: The total number of patients was 39 with 19 males (48.7%) and 20 females(51.3%). The age of patients ranged from 15 years to 70 years. The mean age was 43.41 ±16.57. The most common pathology leading to gastric outlet obstruction was malignancy, in 21 (53.8%) patients whereas 18 patients (46.2%) had benign disease. Among the malignancies, gastric carcinoma was the most common disease affecting 14 patients (35.9%) and among the benign diseases, caustic injury induced stenosis was the most common, involving 14 patients (35.9%). Pancreatic carcinoma was found in 3 patients (7.7%) and peptic ulcer disease in 4 patients (10.3%). Conclusion: Gastric outlet obstruction is a serious and difficult to manage problem. Malignancy was the most common cause (53.8%) of gastric outlet obstruction. Post caustic gastric outlet obstruction has emerged as the second most common(35.9%) cause. Caustic stricture leading to gastric outlet obstruction is emerging as a serious health care issue in developing countries, especially among young females with poor socioeconomic status.